Definitive liver radiotherapy for intrahepatic cholangiocarcinoma with extrahepatic metastases - Brian De; Rituraj Upadhyay; Kaiping Liao; Tiffany Kumala; Christopher Shi; Grace Dodoo; Joseph Abi Jaoude; Kelsey L. Corrigan; Gohar S. Manzar; Kathryn E. Marqueen; Vincent Bernard; Sunyoung S Lee; et al. (Liver Cancer, 2023)
Introduction: Tumor-related liver failure (TRLF) is the most common cause of death in patients with intrahepatic cholangiocarcinoma (ICC). Though we previously showed that liver radiotherapy (L-RT) for locally advanced ICC is associated with less frequent TRLF and longer overall survival (OS), the role of L-RT for patients with extrahepatic metastatic disease (M1) remains undefined. We sought to compare outcomes for M1 ICC patients treated with and without L-RT.